RAS induced senescence of skin keratinocytes is mediated through Rho‐associated protein kinase (ROCK). Issue 12 (17th September 2021) - Lee, Alex J.; Fraser, Elise; Flowers, Brittany; Kim, Jee; Wong, Kenneth; Cataisson, Christophe; Liu, Huaitian; Yang, Howard; Lee, Maxwell P.; Yuspa, Stuart H.; Li, Luowei
Abstract: Cellular senescence is a well‐documented response to oncogene activation in many tissues. Multiple pathways are invoked to achieve senescence indicating its importance to counteract the transforming activities of oncogenic stimulation. We now report that the Rho‐associated protein kinase (ROCK) signaling pathway is a critical regulator of oncogene‐induced senescence in skin carcinogenesis. Transformation of mouse keratinocytes with oncogenic RAS upregulates ROCK activity and initiates a senescence response characterized by cell enlargement, growth inhibition, upregulation of senescence associated β‐galactosidase (SAβgal) expression, and release of multiple pro‐inflammatory factors comprising the senescence‐associated secretory phenotype (SASP). The addition of the ROCK inhibitor Y‐27632 and others prevents these senescence responses and maintains proliferating confluent RAS transformed keratinocyte cultures indefinitely. Mechanistically, oncogenic RAS transformation is associated with upregulation of cell cycle inhibitors p15 Ink4b, p16 Ink4a, and p19 Arf and downregulation of p‐AKT, all of which are reversed by Y‐27632. RNA‐seq analysis of Y‐27632 treated RAS‐transformed keratinocytes indicated that the inhibitor reduced growth‐inhibitory gene expression profiles and maintained expression of proliferative pathways. Y‐27632 also reduced the expression of NF‐κB effector genes and the expression of IκBζ downstream mediators. The senescence inhibition from Y‐27632 was reversible, and upon its removal, senescence reoccurred in vitro with rapid upregulation of cell cycle inhibitors, SASP expression, and cell detachment. Y‐27632 treated cultured RAS‐keratinocytes formed tumors in the absence of the inhibitor when placed in skin orthografts suggesting that factors in the tumor microenvironment can overcome the drive to senescence imparted by overactive ROCK activity.